Relationship Between The Level Of Knowledge Of Breastfeeding Mothers With The Provision Of Colostrum And Breast Milk In Village Health Pos Sitio II In 2020 - Mastiur Julianti Butar Butar; Esther Siringo-ringo; Indah Yani Tambunan (International Archives of Medical Sciences and Public Health, 2022)
This study aimed to determine the relationship of the level of knowledge of breastfeeding mothers with the provision of colostrum and exclusive breastfeeding in Poskesdes Sitio-II Lintongnihuta District in 2020. The data used in this study were primary data by distributing questionnaires to the sample/respondent. By using the Slovin approach from 96 populations got sample as 49 respondents was determined by applying random sampling. The results showed that the relationship between the level of knowledge of breastfeeding mothers with the provision of Colostrum and exclusive breastfeeding in Poskesdes Sitio II, Lintongnihuta District in 2019-2020 can be categorized very strongly, this can be proven by the Correlation Coefficient value of 0.709. Descriptive research results also indicate that the majority of respondents had a very good level of knowledge about the importance of Colostrum. The results of research on the relationship of the level of knowledge of nursing mothers with exclusive breastfeeding in 2019-2020 in Poskesdes Sitio II, Lintongnihuta District had a strong relationship with a correlation coefficient of 0.663. Respondents also answered that giving exclusive breastfeeding to infants can help families in terms of economics, exclusive breastfeeding is also more practical and efficient, given the average breastfeeding mothers who were respondents in this study worked to help her husband as a farmer. The results of this study also indicate the value of Sig = 0,000 <? = 0.05) so that it can be concluded that there was a very significant relationship between the level of knowledge of breastfeeding mothers with the provision of Colostrum and exclusive breastfeeding in Poskesdes Sitio-II Subdistrict of Lintongnihuta in 2019-2020.